Protonation Equilibria of L-Aspartic, Citric and Succinic Acids in Anionic Micellar Media - P. Srinivasa Rao; B. Srikanth; V. Samba Siva Rao; C. Kamala Sastry; G. Nageswara Rao (E-Journal of Chemistry)
The impact of sodium lauryl sulphate (SLS) on the protonation equilibria of L-aspartic acid, citric acid and succinic acid has been studied in various concentrations (0.5-2.5% w/v) of SLS solution maintaining an ionic strength of 0.16 mol dm-3 at 303 K. The protonation constants have been calculated with the computer program MINIQUAD75 and the best fit models have been calculated based on statistical parameters. The trend of log values of step-wise protonation constants with mole fraction of the medium has been explained based on electrostatic and non-electrostatic forces operating on the protonation equilibria. The effects of errors on the protonation constants have also been presented.